The Politics of Nationhood - Lynch, P. author. aut Link
XIII, 201 p.
Keywords: For over a century the Conservative Party has been identified as the patriotic party defending the nation state and British identity. Thatcherism sought to rework the Conservative politics of nationhood in the light of changed circumstances, but the Thatcher and Major Governments faced significant problems managing the Union, European integration and a multicultural society. Philip Lynch examines the key developments and statecraft problems in the conservative politics of nationhood during the Thatcher and Major period.